Cymbidium biflorens (Orchidaceae; Epidendroideae), a new species from China: evidence from morphological and molecular data - Zhang, Di-Yang; Tu, Xiong-De; Liu, Bin; Liao, Xing-Yu; Lan, Si-Ren; Liu, Zhong-Jian (Phytotaxa, 2020)
A new species of Cymbidium (Orchidaceae), Cymbidium biflorens, from Yunnan Province, China, is illustrated and described based on morphological and molecular evidence. Morphological comparison indicates that C. biflorens is similar to C. rhizomatosum, but differs by its leafless, coralline rhizome, normally two flowering periods, a shorter scape, inflorescence with 1–2 flowers, greenish flowers with longer pedicel and ovary, subelliptic petal, petals and lip not fully opened. Molecular analyses base on nuclear (ITS) and plastid DNA (matK and rbcL) were conducted to explore the phylogenetic position of the species. The molecular evidence supports C. biflorens as sister to C. rhizomatosum.